Teaching diversity relationally : engaging emotions and embracing possibilities - Kim, Grace S.; Donovan, Roxanne A.; Suyemoto, Karen L. (New York, NY : Routledge, 2022)
"This book offers process-oriented guidance for negotiating the psychological and relational challenges inherent in teaching about race, privilege, and oppression. Grounded in the philosophy of Transformative Education and incorporating psychological theories, the authors present concrete strategies for effectively teaching diversity and social justice courses. The authors provide guidance on how to prepare for social justice education that fosters the growth of learners and educators by addressing intersecting levels of engagement-intrapsychic (within individual students and educators), relational (between students, between faculty and students), and group dynamic"--
Keywords: Social justice and education; Transformative learning; Social justice -- Study and teaching; EDUCATION / General